Penerapan Program Tahfidz Al-Quran untuk Meningkatkan Kemampuan Literasi Siswa Madrasah Aliyah Ar-Rahman Ciamis - Iing Nurhidayat (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
The research background is the condition of the Madrasah Gead, who must be able to design the direction of educational institutions on a civilized path so that the institution will continue to exist and be able to maintain the continuity of education to become a